2021
DOI: 10.1038/s41422-021-00595-6
|View full text |Cite|
|
Sign up to set email alerts
|

Receptome profiling identifies KREMEN1 and ASGR1 as alternative functional receptors of SARS-CoV-2

Abstract: Host cellular receptors play key roles in the determination of virus tropism and pathogenesis. However, little is known about SARS-CoV-2 host receptors with the exception of ACE2. Furthermore, ACE2 alone cannot explain the multi-organ tropism of SARS-CoV-2 nor the clinical differences between SARS-CoV-2 and SARS-CoV, suggesting the involvement of other receptor(s). Here, we performed genomic receptor profiling to screen 5054 human membrane proteins individually for interaction with the SARS-CoV-2 capsid spike … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
104
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(120 citation statements)
references
References 70 publications
1
104
0
3
Order By: Relevance
“…Together, the results presented in this study indicate that mutations that emerged in the new SARS-CoV-2 Omicron variant enhance the binding affinity of this variant to the host ACE2 receptor, which likely is an important driver of its increased transmissibility. However, it is important to note that SARS-CoV-2 besides ACE2 could also use other cellular receptors as a secondary binding way to target the host cells [19,[41][42][43]. Thus, it cannot be excluded that the changes that emerged in the Omicron viral spike could have an impact on the virus interaction with these secondary cellular receptors, additionally increasing the virus's ability to reach its target.…”
Section: Resultsmentioning
confidence: 99%
“…Together, the results presented in this study indicate that mutations that emerged in the new SARS-CoV-2 Omicron variant enhance the binding affinity of this variant to the host ACE2 receptor, which likely is an important driver of its increased transmissibility. However, it is important to note that SARS-CoV-2 besides ACE2 could also use other cellular receptors as a secondary binding way to target the host cells [19,[41][42][43]. Thus, it cannot be excluded that the changes that emerged in the Omicron viral spike could have an impact on the virus interaction with these secondary cellular receptors, additionally increasing the virus's ability to reach its target.…”
Section: Resultsmentioning
confidence: 99%
“…This type of HERV activation mediated by an interaction between a triggering virus and a specific receptor on certain cells has already been described, e.g., with HHV-6A [33]. Because SARS-CoV-2 induced HERV-W ENV expression in human lymphoid cells that neither express ACE2 nor TMPRSS2 and does not infect them, additional undetermined receptors are expected to mediate HERV activation by SARS-CoV-2, which should now be further studied with recent data on alternative receptors [80].…”
Section: Discussionmentioning
confidence: 84%
“…It is to be noted that apart from ACE2, recent research [14] has identified cellular proteins like asialoglycoprotein receptor-1 (ASGR1) and Kringle Containing Transmembrane Protein 1 (KREMEN1) as SARS-CoV-2 receptors in Spike glycoprotein. The authors in [14] have shown that both RBD and N-terminal domain bind of Spike glycoprotein bind to ASGR1 and KREMEN1. These two proteins are also believed to affect the viral target cell range as well as antibody-mediated neutralization [16] .…”
Section: Discussionmentioning
confidence: 99%